Offenders on offending : learning about crime from criminals - Bernasco, Wim (Taylor and Francis, 2011)
Our knowledge of crime is based on three types of sources: the criminal justice system, victims, and offenders. For technological and other reasons the criminal justice system produces an increasing stream of information on crime. The rise of the victimization survey has given the victims a much larger role in our study of crime. There is, however, no concomitant development regarding offenders. This is unfortunate because offenders are the experts when it comes to offending. In order to understand criminal behavior, we need their perspective. This is not always a straightforward proc.